(untitled) (Global Journal of Science Frontier Research, 2021)
The article presents a new and effective way to solve a psychophysical problem or the problem of the mind-body relationship. The psychophysical problem is a scientific task of a universal human scale, which requires a revision of the fundamental foundations of modern science and creating a new scientific and philosophical concept. The scientific article presents some of the results of our previous work: the place and function of viruses in nature, a new classification of the genome, and a nano-model theory of the functioning of the genome. These made it possible to revise the cell theory, to understand the mechanisms of the formation of human higher nervous activity, and to formulate a new scientific and philosophical concept of the universe. Understanding the mechanisms of interaction between mind and body will contribute to the intensive development of the health care system, education system, psychology, neuro-linguistics, sociology, and many other practical areas.